2020
DOI: 10.7554/elife.59073
|View full text |Cite
|
Sign up to set email alerts
|

Re-expression of SMARCA4/BRG1 in small cell carcinoma of ovary, hypercalcemic type (SCCOHT) promotes an epithelial-like gene signature through an AP-1-dependent mechanism

Abstract: Small cell carcinoma of the ovary, hypercalcemic type (SCCOHT) is a rare and aggressive form of ovarian cancer. SCCOHT tumors have inactivating mutations in SMARCA4 (BRG1), one of the two mutually exclusive ATPases of the SWI/SNF chromatin remodeling complex. To address the role that BRG1 loss plays in SCCOHT tumorigenesis, we performed integrative multi-omic analyses in SCCOHT cell lines +/- BRG1 reexpression. BRG1 reexpression induced a gene and protein signature similar to an epithelial cell and gained chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 79 publications
4
16
0
Order By: Relevance
“…In our analysis, genes overexpressed in SCCOHT, compared with ECRT SMARCB1 , included those related to intercellular adhesion and neurogenesis, whereas genes overexpressed in ECRT SMARCB1 included those related to skeletal morphogenesis. Interestingly, the observed overexpression of intercellular junction genes in SCCOHT could be in keeping with a recent study which found that re‐expression of SMARCA4 induced an epithelial‐like gene and protein expression programs in SCCOHT cell lines [49]. In addition, we found several transcription factors and HOX genes to be differentially expressed between SCCOHT and ECRT SMARCB1 .…”
Section: Discussionsupporting
confidence: 91%
“…In our analysis, genes overexpressed in SCCOHT, compared with ECRT SMARCB1 , included those related to intercellular adhesion and neurogenesis, whereas genes overexpressed in ECRT SMARCB1 included those related to skeletal morphogenesis. Interestingly, the observed overexpression of intercellular junction genes in SCCOHT could be in keeping with a recent study which found that re‐expression of SMARCA4 induced an epithelial‐like gene and protein expression programs in SCCOHT cell lines [49]. In addition, we found several transcription factors and HOX genes to be differentially expressed between SCCOHT and ECRT SMARCB1 .…”
Section: Discussionsupporting
confidence: 91%
“…AP-1 is a transcription factor that contains dimers of the Jun and Fos proteins with known pro-oncogenic and anti-oncogenic roles [ 27 ]. As it pertains to normal SWI/SNF and AP-1 interactions, their relationship has been increasingly linked to anti-oncogenic processes [ 7 , 25 , 30 , 31 ] where it is thought that AP-1 and SWI/SNF interact through the BAF60a SWI/SNF subunit [ 26 , 32 ] to allow for enhancer selection and activation of cell fate and differentiation gene expression programs [ 26 ]. However, in our study the sites with reduced chromatin accessibility are not associated with cell fate and differentiation genes but rather pro-oncogenic gene categories such as migration, signal transduction, and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…1c-e), suggesting that SWI/SNF components are preserved at conserved MYC sites. Next, to relate our findings to additional cancer settings, we compared binding of MYC-SWI/SNF to BAF155 detected in BRG1-deficient small cell carcinoma of the ovary, hypercalcemic type (SCCOHT), which like MRT is both rare and aggressive and tumorigenesis has been linked directly to multiple mechanisms resulting from loss of a single SWI/SNF subunit (25,26). Remarkably, almost all MYC-SWI/SNF peaks in MRT overlap with chromatin-bound BAF155 that remains following BRG1 loss in the SCCOHT cell line, BIN67, (Fig.…”
Section: Baf155 Is Present At Myc-swi/snf Bound Sites In Other Tumor Cell Typesmentioning
confidence: 99%